Synthesis and comparison of photo-catalytic oxidation (PCO) of Fe₂O₃/TiO₂, Fe₃O₄/TiO₂ and Fe₃O₄/SiO₂ nanoparticles - Ji, Baoyan (Nanyang Technological University, 2022)
The occurrence of some organic contaminants, such as total organic carbon (TOC) in wastewater treatment and water purification is attracting significant concerns because some of them are highly toxic and will pose risk to the environment. Large quantities of these pollutants (from domestic, agricultural, or industrial effluent) are produced every day and released onto aquatic bodies. Traditional wastewater treatment methods are ineffective for the degradation of these pollutants. Although there are advanced technologies adopted, such as granular activated carbon (GAC) adsorption, ozonation, hydrogen peroxide, chlorination, etc., they have drawbacks of high cost, time-consuming, energy intensive and further disposal of waste generated is necessary. Therefore, it is essential to develop sustainable and efficient TOC removal technologies. Photocatalytic oxidation (PCO) is one of the most promising techniques to treat organic pollutants in wastewater. As semiconductor nanomaterials, TiO2 and SiO2 are the commonly studied photocatalyst because of their low cost, availability, high chemical and thermal stability, and more importantly, they are safe for the environment. However, the wide band gap of TiO2 has made it only active under UV irradiation. In addition, SiO2 exhibits a very wide bandgap, and it has low solubility and slow reaction time in water. Hence, bare TiO2 or SiO2 is not an ideal photocatalyst for the PCO reaction. To address these limitations, Fe3O4-TiO2, Fe2O3-TiO2 and Fe3O4-SiO2 nanocomposites were synthesized in this paper, and they were to be used as an active photocatalyst for the photodegradation of TOC under a UV lamp irradiation. Fe2O3 and Fe3O4 were used as dopants ascribe to their exclusive properties such as magnetic properties and low bandgap. Several characterizations were performed to study the size, morphology, crystallinity, and elemental composition of the prepared nanocomposites. Photoactivity was measured via UV-Vis spectrophotometer to check the ability of the nanocomposite absorbs light, as well as the TOC concentration before and after the PCO reaction. The photocatalytic evaluation showed Fe2O3-TiO2 demonstrated the best performance among all synthesized photocatalysts. Finally, future research needs are also highlighted.